Are There Modifiable Risk Factors to Improve AKI?. (4th July 2017) - Nie, Sasa; Tang, Li; Zhang, Weiguang; Feng, Zhe; Chen, Xiangmei
Abstract : Acute kidney injury (AKI) is a common critical syndrome, with high morbidity and mortality. Patients with AKI typically have an adverse prognosis, from incident chronic kidney disease (CKD), progression to end-stage renal disease (ESRD), subsequent cardiovascular disease, and ultimately death. However, there is currently no effective therapy for AKI. Early detection of risk factors for AKI may offer a good approach to prevention or early intervention. Traditional risk factors include extreme age, many common comorbid diseases, such as preexisting CKD, some specific exposures, such as sepsis, and exposure to some nephrotoxic agents. Recently, several novel risk factors for AKI, such as hyperuricemia, hypoalbuminemia, obesity, anemia, and hyperglycemia, have been identified. The underlying mechanisms between these nontraditional risk factors and AKI and whether their correction can reduce AKI occurrence remain to be clarified. This review describes the current epidemiology of AKI, summarizes its outcome, outlines the traditional risk profile, and finally highlights some recently identified novel risk factors.